APLICACION DEL ANALISIS DE IMAGENES AL ESTUDIO DE PARÁMETROS MORFOMETRICOS DEL CORCHO - Campos, M.; Molinas, M. (Scientia gerundensis, 1999)
In this work we propose a method to study cork quality from little samples throug the analy- sis of images. This method has aplications in all studies that need cork quality determination. The digital analysis of images is an apropiate option due to makes morphometry automati- cally and it allows a quick manipulation of the results. It is a fast and objective method because allows the comparative study between a high number of samples; so it could be pos- sible to compare populations or individual in order to study the influence of some ambiental or getnetic factors and have another aproach to three's selection. Here we describe an digital analysis program based on IMAGE 1.41 VDMi software for Macintosh developed to measu- re severa1 cork morphometric parameters.
Keywords: Cork quality; image analysis; methodology; morphometry; Quercus suber

Efecto de los tratamientos silvopastorales en el crecimiento del alcornoque - Caritat, A.; Molinas, M.; Vilar, L.; Masson, Ph (Scientia gerundensis, 1999)
Comparative effects of shrub clearing and grazing on the apical and radial growth of the cork oak have been studied in four cork oak wood stations. Shoot growth segments and annual wood rings were measured in 10 selected trees in every plot. Average shoot elongation's oscillate between 2.5 to 4.8 cm; annual wood rings from 0.95 to 2.05 mm and annual radial growth of wood plus cork from 2.3 to 5.7 mm. Significative differences were found between silvo-pastoral treatments in relation to apical elongation. In treated plots, the apical growth of segments that reach the maximum elongation can be a 75% higher than in control plots. This increment on shoot growth can be explained by the decrease in plant competition and by the nutrient contribution of grazing. No significative effects of treatments on radial growth have been found.
Keywords: Alcornoque; crecimiento apical; Crecimiento radial; desbroce; pastoreo (voyant)

Annual cork-ring width variability of Quercus suber L. in relation to temperature and precipitation (Extremadura, southwestern Spain) - Caritat, A.; Molinas, M.; GUTIÉRREZ, E. (Forest Ecology and Management, 1996)
A 14 year sequence of cork-ring width chronology is correlated with rainfall and temperature data. Cork specimens were obtained from three cork peel samplings carried out in 1989, 1991 and 1993 from a cork ‘dehesa’ in Ckeres, Spain. Average width of cork-rings varied between 2.05 and 4.37 mm. The cork-ring width chronologies of the three peel-off samplings show definite agreement patterns. Differences in ring width in years of greater and lesser growth are clearly marked. Correlation between ring width and rainfall indicates that the rain periods with the greatest influence on cork growth are those occurring from November to June, followed by those from November to September. Temperature, on the other hand, shows a negative correlation with cork growth, except during the coldest months and the months of April and September when temperature possibly has a crucial influence on phellogen activation.
Keywords: climatic fluctuations; cork growth; cork-oak; cork-ring chronology; Quercus suber L.

Litterfall and mineral return in two cork-oak forests in northeast spain - Caritat, A.; Bertoni, G.; Molinas, M.; Oliva, M.; Domínguez-Planella, A. (Ann. For. Sci., 1996)
Seasonal trends in littertall and potential mineral return were studied in two cork-oak forest sites in the northeastern Iberian peninsula. The estimated average litter production was 3.9 Mg.ha-1.year -1 for one site and 4.6 Mg.ha-1.year-1 for the other; these figures are similar to those reported for holm-oak (Quercus ilex) forests in the same area. Seasonal litterfall patterns were typical of Mediterranean forest ecosystems. Leaves accounted for 46 to 78% of the total dry matter. Their annual weighted-average mineral composition was low in macronutrients (N 8-9; K 4-5; Mg 0.8-1.3; Ca 9-10 and P 0.4-1 mg.g-1) and relatively high in micronutrients such as Mn (2-2.2 mg.g-1) or Fe (0.3-0.4 mg.g-1). Minimum N and P concentrations were found during the growth period. Estimates of potential mineral return for an annual cycle were N 38-52, P 2.1-5.2, K 20-28, Ca 44-53 and Mg 5.4-5.0 kg.ha -1, depending on the site biomass and fertility.
Keywords: cork-oak; litterfall; Mediterranean forest ecosystems; nutrient cycling; Quercus suber

Nutrient content and seasonal fluctuations in the leaf component of coark-oak (Quercus suber L.) litterfall - Robert, B.; Caritat, A.; Bertoni, G.; Vilar, L.; Molinas, M. (Plant Ecology, 1996)
Nutrient content and seasonality of the leaf component in cork-oak litterfal were studied over a two year period in two cork-oak forest sites differing in biomass and edaphic condition in the north-eastern Iberian peninsula. Fallen senescent leaves compared to young leaves showed higher non-mobile nutrient concentrations and lower mobile nutrient concentrations, specially P, N, K, and Mg. At both sites, seasonal fluctuations affected both leaf production and leaf mineral content. The maximum leaf fall period correspond to the start of the vegetative growth and to the lowest N and P concentration in the falling leaves. The opposite was true for the winter, when litterfal was minimal and N and P content in falling leaves was at a maximum. The comparison between falling leaves and canopy leaves suggests that the analysis of fallen leaves can be a useful measure of N and P nutrition in cork-oak. We found site dependent differences in nutrient content and nutrient remobilization. In comparison with Q. ilex, although litter production was in the same range, nutrient retranslocation was greater for Q. suber.
Keywords: litterfall; nutrient return; nutrients in leaves; Quercus Suber L; retranslocation; seasonal trends

El crecimiento radial del alcornoque en cinco parcelas de alcornocal de Girona - Caritat, A.; Molinas, M.; Oliva, M. (Scientia gerundensis, 1992)
Tree rings of Quercus suber L. are porous and difficult to read because of the irregular growth rhythm. Radial growth has been measured in five experimental plots situated in the region of Girona (Catalonia, NE Spain). Cores of ten standard trees of each plot were extracted using a Pressler borer. In three plots woody disks from standard trees were also obtained. Tree rings were examinated under binocularlens. The CATRAS computer program (Anio1,1983 ) was used to find statistical parameters. Tree rings have an average width changing from 1,21 to 3,74 mm, while average standard deviation varies from 0,24 to 1,88 mm. and autocorrelation from 0,008 to 0.894 . These values are similar to those found in other Mediterranean Quercus, like Q. ilex L. The studied cork-oak plots ,with diametrical classes between 5 and 57 cm, show regular growth characteristic of young forest. The St. Hilari plot has the maturest trees, (diametrical classes from 24 to 57 cm) and this fact was reflectedin thegrowthcurve. Suddengrowthincreases are attributed to forestry management measures like clearing or selective cutting down. The effects of periodic cork extractions could no be clearly appreciated in this study.
Keywords: cork-oak; Mediterranean sclerophylls; Quercus suber L.; Radial growth; wood rings